Analysis and design of enhanced planar devices using multiconductor transmission lines with interconnected alternate lines - Sánchez-Martínez, Juan José (Universidad de Málaga, Servicio de Publicaciones y Divulgación Científica, 2014)
Novel capabilities and applications of multiconductor transmission lines with interconnected alternate lines have been analyzed in this work. The interconnections among alternate strips broaden the operating frequency band by eliminating undesired resonances and allow the use of simplified analytical models. Phase shifters, baluns, reconfigurable systems for the characterization of balanced circuits, ultra-wideband differential bandpass filters and quasi-elliptic bandpass filters have been proposed and demonstrated. For all these circuits a systematic design procedure have been derived and validated by means of experimental work. The excellent agreement between the measurements and the predicted results validates the proposed procedures as reliable and quick design techniques.
Keywords: Líneas de telecomunicaciones - Tesis doctorales; Balun; Coupled lines; Differential filter; Multiconductor transmission lines; Quasi-elliptic bandpass filters